ANALISIS PERTUMBUHAN, PENYERAPAN TENAGA KERJA DAN KEMISKINAN PROVINSI SUMSEL - Wibowo, Tri (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2013)
Sychronize with the national development strategy of development in the province of South Sumatra is pro-growth , pro- jobs , and pro-poor. South Sumatra Province has a major contribution in the national economy, with a 3 percent contribution to the national economy. South Sumatra province have overcome employment, but need an acceleration in economic growth and poverty reduction. The results of the analysis of the typology Klassen, 10 districts/cities or 2/3 which is in South Sumatra Province, located in the rapidly growing phase. Development in South Sumatra province to be prioritized to 10 districts/cities that are still ready for the growing attention for the labor-intensive sectors, such as agriculture and industry, so that the level of unemployment and poverty can be reduced for the acceleration of an inclusive growth. The results of the sensitivity analysis showed that the increased 1 percent of economic growth, generate employment amounted to 11.05 thousand people and reducing poverty by 11.08 thousand people.